PENGEMBANGAN COMICS OF BIOLOGY EXPERIMENTAL GUIDE UNTUK KELAS VII SMP RSBI - -, Griyani; Habibah, Noor Aini; Pukan, Krispinus Kedati (Journal of Biology Education, 2013)
This study determined the development process and feasibility ofÂ  Comics of Biology Experimental Guide as a teaching material. This study used Research and Development (R & D). It was conducted at SMP 5 Semarang and SMP 21 Semarang. In obtaining the feasibility proof of this book as a teaching material, the study used questionnaire. Data were analyzed by using descriptive percentages. Based on the criteria of the feasibility, the results showed that this book guide is very feasible. It was able to achieve the graduation classical > 85% with KKM 75.Â Penelitian ini bertujuan untuk mengetahui proses pengembangan Comics of Biology Experimental Guide dan kelayakannya sebagai bahan ajar. Metodepenelitian yang digunakanadalahResearch and Development (R & D). Penelitian ini dilaksanakan di SMP 5 dan 21 Semarang. Penelitianini menggunakan metodeangketuntukmemperolehbuktiidentifikasikelayakan buku petunjuk praktikum Comics of Biology Experimental Guide sebagai bahan ajar.Data dianalisismenggunakandeskriptifpersentase.Hasilpenelitianmenunjukkanbahwapenilaiankelayakan buku petunjuk praktikum Comics of Biology Experimental Guide sesuaicriteriayaitusangatlayak. Buku petunjuk praktikum Comics of Biology Experimental Guide ini mampu mencapai kelulusan klasikal > 85% dengan KKM 75